Subjective cognitive decline is longitudinally associated with lower health-related quality of life - Röhr, Susanne; Weyerer, Siegfried (International psychogeriatrics, 2017)
Background: Subjective cognitive decline (SCD), the potentially earliest notable manifestation of preclinical Alzheimer's disease and other dementias, was consistently associated with lower quality of life in cross-sectional studies. The aim of this study was to investigate whether such an association persists longitudinally - particularly with health-related quality of life (HRQoL) in older individuals without cognitive impairment. Methods: Data were derived from follow-up 2-6 of the prospective Germany Study on Ageing, Cognition and Dementia in Primary Care (AgeCoDe) covering a total six-year observation period. We used linear mixed effects models to estimate the effect of SCD on HRQoL measured by the EQ-5D visual analogue scale (EQ VAS). Results: Of 1,387 cognitively unimpaired individuals aged 82.2 years (SD = 3.2) on average, 702 (50.6%) reported SCD and 230 (16.6%) with SCD-related concerns. Effect estimates of the linear mixed effects models revealed lower HRQoL in individuals with SCD (unadjusted: -3.7 points on the EQ VAS, 95%CI = -5.3 to -2.1; SE = 0.8; p < 0.001; adjusted: -2.9 points, 95%CI = -3.9 to -1.9; SE = 0.5; p < 0.001) than in individuals without SCD. The effect was most pronounced in SCD with related concerns (unadjusted: -5.4, 95%CI = -7.6 to -3.2; SE = 1.1; p < 0.001; adjusted: -4.3, 95%CI = -5.8 to -2.9, SE = 0.7; p < 0.001). Conclusion: SCD constitutes a serious issue to older cognitively unimpaired individuals that is depicted in persisting lower levels of HRQoL beyond depressive symptoms and functional impairment. Therefore, SCD should be taken seriously in clinical practice.